Implementation of the Paddy Field Pawn System in Karangdoro Village, Tegalsari District from the Perspective of Fiqh Muamalah - Mukaromah, Inggrit Lailatul; Munawir, Munawir (SAINTIS Publishing, 2025)
The purpose of this study is to find out the pawn system sold in Karangdoro Village, Tegalsari District, Banyuwangi Regency and the perspective of muamalah fiqh on the practice of the paddy field pawn system in the village. The formulation of the problem is how to implement the pawn system in Karangdoro village and whether the pawn system is in accordance with the perspective of fiqh muamalah. The research method used is qualitative in the form of a case study. The data was obtained through interviews with one of the people of Karangdoro Village as a pawn perpetrator (rahin and murtahin) and the Secretary of Karangdoro Village as well as documentation of the practice of pawning rice fields. The validity test of the data uses credibility, transferability, dependability, and confirmability. Data analysis techniques use data reduction, data display, and conclusion drawn. The results of the research revealed that the pawn system in Karangdoro Village was due to economic pressure, rahin and murtahin agreed with the terms written in the agreement. The pawn system in Karangdoro Village is in accordance with the perspective of muamalah fiqh because it has fulfilled the harmony and conditions of pawn, namely the existence of rahin and murtahin that are mukalaf and not prevented from tasaruf, marhun or goods pawned in the form of rice fields, marhun bih or debt in the form of money that must be returned rahin to murtahin, and clear shighot.